Automatización en el llenado de los camiones cisterna en los planteles de RECOPE - Castillo-Rojas, Douglas (Instituto Tecnológico de Costa Rica, 2012)
The current form of loading the tank motor vehicles in RECOPE campuses generates operational safety issues and also long filling times. That is why before the modernization sales campus located in Moin refinery, is intended to change the form filling vehicles with the purpose of solving the present problems with the current form, to reduce hazards and get the attention of more users. Thus arises the need to analyze the equipment to be used by tankers to ensure operation with the system to be installed in the islands filling and satisfying dictated by the API RP 1004. Thus would provide the minimum requirements necessary to solve the problem at hand.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2012.
Keywords: Carga ventral; Cisternas; Sistemas; Combustibles; Petróleo; RECOPE; Refinadora Costarricense de Petróleo